Coding Metasurfaces: Ultrawideband Spin‐Decoupled Coding Metasurface for Independent Dual‐Channel Wavefront Tailoring (Ann. Phys. 3/2020). Issue 3 (12th March 2020) - Guo, Wen‐Long; Wang, Guang‐Ming; Luo, Xin‐Yao; Hou, Hai‐Sheng; Chen, Ke; Feng, Yijun
Abstract : In article number 1900472 by Ke Chen, Yijun Feng, and co‐workers, a coding methodology is reported that can enable a metasurface with independent 1‐bit phase codes for orthogonal spins. The proposed method is verified by two spin‐decoupled meta‐devices for either electromagnetic beam deflecting or generating multi‐beams carrying desired orbital angular momentums.